A Hayekian Explanation of Hayek's "Epistemic Turn" - Scott Scheall (Duke University, Center for the History of Political Economy (CHOPE), 2014)
The present essay investigates F.A. Hayek's epistemology and his methodology of sciences of complex phenomena for implications relevant to an explanation of Hayek's own so- called "epistemic turn." The thesis defended here is that Hayek's dissatisfaction with his technical economics – in particular, his business cycle project – prompted, in keeping with his evolutionary theory of belief revision, the develo pment of an approach less susceptible to the same disappointment.
Keywords: B2; B25; B3; B31; B4; B41; B53; 330; Hayek; epistemic turn; methodology; complex phenomena; explanation of the principle